Teaching Vocabulary Using the Duolingo Application in Junior High School - Dhea Anggita Putri Ningtyas; Dian Reftyawati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Most students in junior high school, especially seventh grade, had difficulty learning vocabulary. Even though vocabulary was very important for language learning. Duolingo could help with this problem because Duolingo could make students more interested and less bored when studying. The purpose of this research was to find out whether there was an effect of the Duolingo Application in increasing the vocabulary mastery of 7th grade students at SMPN 32 Bandar Lampung in the 2023/2024 academic year. This research methodology used in this research was quasi-experimental design. The population of this research was all 7th grade students of SMP Negeri 32 Bandar Lampung for the 2023/2024 academic year with a total of 180 students. This research sample consisted of two classes, namely class 7B with a total of 34 students as the experimental class, and class 7C with a total of 33 students as the control class. This meant that the total number of samples for this research was 67. The experimental class used Duolingo Application, while the control class used the “When English Rings a Bell” textbook and dictionaries. The sample for this research was determined using a cluster random sampling technique. The treatment was carried out in first meeting. In collecting data, this research used a test instrument in the form of 40 multiple choice questions. Before giving treatment, a pretest was carried out. Then, after the treatment has been carried out, a post test was given. The results showed that there is a significant difference in student scores before and after treatment. This research used hypothesis testing, especially the T-test, to find out whether the Duolingo Application had a significant effect on students' vocabulary scores. And the results show that Sig. (ρvalue) = 0.000 < α = 0.05. So Ha is accepted and Ho is rejected. It can be concluded that there is a significant effect of using the Duolingo Application on increasing the vocabulary mastery of 7th grade students at SMP Negeri 32 Bandar Lampung in the 2023/2024 academic year.